The Architectural Heritage: Treasures Deserve Care and Investigations (Cave Houses in Gharyan City as a Model) (Journal of Libya for geographical studies, 2021)
Preserving the urban heritage has become a human historical responsibility that contributes to preserving the landmarks of the past for future generations to see. Since man became aware of the historical inevitability of the past, present and future, he tried to record his present and preserve his past to see the future , The urban heritage gas become a reflection of the civilized identity of man; its past, present and future. And with the continued cultural invasion of western civilizations in the Third World, where the preservation of cultural identity has become through the preservation of urban heritage.The study illustrates Gharyan s' Potential Of Cultural heritage and ist diversity, especially urban, It confirms its importance and the need to preserve and exploit it to promote tourism, especially Cultural and historical ones.The study Concluded that past may live in the present, but it may also be denied, depending on the extent to which governments and societies are aware of the importance and value of their cultural and civilizational heritage or not. And to devote efforts through various activities, including tourism, to save what remains of human heritage from the encroachment of rafts of sabotage and neglect.
Keywords: urban heritage; digging houses; Gharyan City